synthesis and characterization of hematite Fe2O3 nanofiller for enhanced dielectric and microwave-absorbing properties in PTFE composites - Alhaji, Bello Murtala; Azis, Raba’ah Syahidah; Shabdin, Muhammad Kashfi; Osman, Nurul Huda (Penerbit UniMAP (UniMAP Press), 2024)
This paper presents the synthesis of hematite Fe2O3 nanofiller from mill scales and its application in polytetrafluoroethylene (PTFE) composites for enhanced dielectric and microwave-absorbing properties. The nanofiller was obtained through 9 hours of high-energy ball milling, resulting in a particle size reduction 43.6 to 11.05 nm. The PTFE/Fe2O3 composites were fabricated by dispersing different concentration of Fe2O3 nanofillers using the dry powder processing technique. The structural and morphological characterization of the nanofiller and PTFE/Fe2O3 composites was carried out using X-ray diffraction (XRD) and field emission scanning electron microscopy (FESEM), respectively. The composites’ microwave absorption properties were analyzed utilizing vector network analyzer (VNA) measurements in the 8–12 GHz frequency range. Based on the findings from the results, as the percentage of filler increased from 5 to 15%wt, the composites' loss tangent and dielectric constant increased from 0.0272 to 0.0478 and 2.12 to 3.25, respectively, while their reduced signal transmission speed was between 2.21 and 2.07 x 108 m/s at 8 GHz and from 2.24 to 2.11 x 108 m/s at 12 GHz. These findings demonstrate that Fe2O3 nanoparticles are a suitable material for developing microwave-absorbing polymer composites within the 8–12 GHz frequency range.